Ocorrência e caracterização molecular de Cryptosporidium spp. E Eimeria spp. em criações comerciais brasileiras de coelhos - Heker, Maísa Melo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The eimeriosis is an important parasitic disease in rabbits, that can host 11 species of Eimeria. Cryptosporidiosis is a zoonotic disease that can be transmitted through food, drinking water and by contact with infected animals and people. The objective of this study was to verify the occurrence of Eimeria spp. and Cryptosporidium spp. in fecal samples of rabbits, perform their molecular classification and relate the presence of the parasites to the different categories in the Brazilian farms. Fecal samples (n = 514) were collected from 21 farms. The oocysts were purified and visualized by microscopy. Fifty five samples positive for Eimeria spp. using microscopy were subjected to polymerase chain reaction (PCR) for amplification of a partial fragment of the ITS1 region of the rRNA gene of Eimeria spp. and the 18S rRNA and the gp60 glycoprotein genes of Cryptosporidium spp.. The microscopy revealed positivity of 19.45% (100/514) for Eimeria spp. and 1.56% (8/514) for Cryptosporidium spp.. The PCR identified E. exigua (14.5%), E. flavescens (61.8%), E. intestinalis (16.36%), E. irresidua (16.4%), E. magna (50.9 %), E. media (3.6%), E. perforans (36.4%), E. piriformis (20.0%), E. stiedai (7.3%) and E. vejdovskyi (7.3 %). Higher positivity was observed in mini rabbits 33.17% (69/208), young rabbits 46.67% (35/75) and in lactating females 24.47% (23/94). Seven samples were positive by PCR (12.73%; 7/55) for Cryptosporidium spp.. Molecular analysis revealed Cryptosporidium cuniculus (18S rRNA) and C. cuniculus subtype VbA21 (gp60) in young rabbits and in does
Keywords: Coccidiose; Criptosporidiose; Microscopia; Reação em cadeia da polimerase; Seqüenciamento de nucleotídeo; Coelho; Eimeria spp